2021
DOI: 10.3390/ijerph181910394
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Cognitive Failure among Nurses during the COVID-19 Pandemic

Abstract: Numerous studies provide evidence of the physical and emotional strain experienced by nurses during the COVID-19 pandemic. However, little is known regarding the impact of this occupational strain on nurses’ cognitive function at work. The aim of this study was to identify factors associated with workplace cognitive failure in a sample of U.S. nurses during the COVID-19 pandemic. An online questionnaire was administered in May 2020 to Michigan nurses statewide via three nursing organizations (n = 695 responden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 63 publications
0
14
0
4
Order By: Relevance
“…Studies have shown that COVID-19, besides leading to somatic changes, may also cause psychic ones, from mild to acute psychiatric symptoms [ 5 , 6 ]. Social distancing and isolation may trigger numerous abnormal reactions, manifested by post-traumatic stress, anger and a sense of loss [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that COVID-19, besides leading to somatic changes, may also cause psychic ones, from mild to acute psychiatric symptoms [ 5 , 6 ]. Social distancing and isolation may trigger numerous abnormal reactions, manifested by post-traumatic stress, anger and a sense of loss [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Beberapa penelitian melaporkan bahwa pada awal pandemi COVID-19, ketersedian APD sangat sedikit sehingga menambah tingkat stress dan rasa lelah pada perawat. Kekhawatiran akan tertularnya virus COVID-19 yang diketahui sebagai penyakit baru dan belum ada pengobatannya menambah kontribusi rasa cemas, kekhawatiran dan lelah perawat (Arnetz et al, 2021).…”
Section: Lainnyaunclassified
“…Perawat yang merawat pasien COVID-19 memiliki kondisi kesehatan dan kelelahan yang jauh lebih buruk jika dibandingkan dengan rekan kerja yang hanya merawat pasien dengan penyakit lain (Arnetz et al, 2021). Kelelahan kerja apabila dibiarkan maka dapat menyebabkan hilangnya produktivitas dan kecelakaan kerja (Tumanggor et al, 2020), (Agustina Hotma Uli Tumanggor, 2018a), (Agustina Hotma Uli Tumanggor, 2018b),…”
Section: Lainnyaunclassified
“…An illustration of noticing is that during this pandemic, people, including nurses, have been overwhelmed with huge volumes of information, at times making it hard to recognise and prioritise key messages. Cognitive exhaustion may impede people's ability to keep up to date with shifting information (Arnetz et a., 2021). Throughout the pandemic thus far we have seen vastly divergent meaning-making about COVID-19, between individuals, communities, and nations.…”
Section: Conceptual Frameworkmentioning
confidence: 99%